Lorenz and Stochastic Dominance Comparisons of European Income Distribution - John A. Bishop; M. John P. Formby; Ryoichi Sakano (Luxembourg Income Study (LIS), 1995)
The goal of this paper is threefold. First, to make stochastic dominance comparisons as well as Lorenz orderings for five European countries. Second, to analyze the changes in distributions across time, and third, to explore whether there is evidence of convergence or divergence in European income distributions. They find that Lorenz curves became significantly more unequal in Sweden and the U.K., did not change significantly in Germany and France, and became more equal in the Netherlands. Their main conclusion is that as of the mid 1980's, European economic integration had not resulted in a convergence of standards of living as measured by rank and generalized Lorenz dominance.
Keywords: 330